(3aJM GdbOhS aj TQM NWHI GdbGehSs - (3CHh GdYHGS CMeO Hf YHO GdYRjR Hf GdQTjO GdSLdeGSi GdTgjQ HGdgdGdis; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3BNQgG (B:s
(3BNQ GdehLhO efgG bhdg GdNWGH (B: (3jbGd NGWHJg NWGHG heNGWHIGi hGLgJg HGdcdGe hGdNWH HGdcSQ GdQLd GdPi jNWH hgh GjVGNWHg s
(3Vef eLehY s
(3HgG fXGe GdJYbjHI HChdgG JQLeg ddTGQM JJab ai ChdgG eY Ghd GdfSNI GdChdi HGNJdGa jSjQ ai HYV GdCdaGXs
(3fSNI KGdKgs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs